Pengaruh Sales Growth dan Struktur Modal terhadap Financial Distress - Neng Wanda Salsa Dila; Ferdiansyah Ritonga (Journal of Trends Economics and Accounting Research, 2024)
This study aims to determine the effect of sales growth and capital structure on financial distress. The study population is consumer non-cyclicals sector manufacturing companies for the period 2018-2022. This study used purposive sampling method sampling techniques to select samples using certain criteria obtained samples of 40 companies for 5 years with a sample of 200. Data analysis was performed using multiple linear regression with the E-views test tool version 12. The results of this study show that the sales growth variable has a probability value of 0.2562 > 0.05 which means that the sales growth variable does not affect financial distress. Meanwhile, the capital structure variable has a probability value of 0.0000 < 0.05 which means that the capital structure variable has a negative and significant effect on financial distress. The implication of this study is that it can be used by company financial managers to manage sales growth and capital structure more effectively to avoid financial distress conditions.